Cuidados de enfermería postquirúrgicos inmediatos en trasplantes de células progenitoras hematopoyéticas: revisión sistemática - Ortíz Solano, Luis Oswaldo (2025)
Introduction: Hematopoietic progenitor cell transplantation consists of the infusion of stem cells, the same which can be autologous or allogeneic, with the aim of re - establishing the medullary and immunological function of the patient with hematological malignant pathologies such as: leukemia, lymphoma, myeloma, non - malignant acquired pathologies of the bone marrow (medullary aplasia), pathologies related to genetics and inadequate hematopoiesis within the medullary function. Objective: To describe the role of nursing in Immediate Post - Surgical Care in Hematopoietic Progenitor Cell Transplantation through the elaboration of a systematic review. Materials and methods: The present research was developed under the qualitative approach, which covers a set of methods and techniques with an interpretative value that aims to describe, analyze, decode, translate and synthesize the meaning of the facts. Discussion: Nursing professionals are a fundamental pillar within the multidisciplinary team, during the whole process of hematopoietic cell transplantation, as they are the professionals who will be in charge of providing specific care throughout the immediate recovery phase in the post - surgical recovery area, as well as in the hospitalization areas where they will remain for a large part of their time, during the duration of the treatment. Conclusions: Hematopoietic cell transplantation is a procedure generally performed on cancer patients with leukemia, lymphomas and myelomas, which is based on the extraction of hematopoietic progenitor stem cells either from the patient (autologous) or from a donor (allogeneic). Finally, the role of nursing professionals in the surgical area is divided into three phases before, during and after transplantation.